# |
ODE |
Mathematica |
Maple |
\[
{}x^{4} y^{\prime \prime \prime \prime }-4 x^{3} y^{\prime \prime \prime }+12 x^{2} y^{\prime \prime }-24 x y^{\prime }+24 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 12 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }+3 x y^{\prime }-3 y = 4 x
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-5 x^{2} y^{\prime \prime }+14 x y^{\prime }-18 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-6 x^{2} y^{\prime \prime }+16 x y^{\prime }-16 y = 9 x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = x \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+3 x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 9 x^{2}
\] |
✓ |
✓ |
|
\[
{}4 x^{4} y^{\prime \prime \prime \prime }+24 x^{3} y^{\prime \prime \prime }+23 x^{2} y^{\prime \prime }-x y^{\prime }+y = 6 x
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+5 x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }-6 x y^{\prime }+6 y = 40 x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = {\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = g \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y = g \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = 2 t^{2}+4 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime } = t +\cos \left (t \right )+2 \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = t +\sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = t^{2} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+y = t +{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = t^{3} {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime } = x^{2}+8
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-12 y = x +{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+y^{\prime }-4 y = {\mathrm e}^{4 x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 n^{2} y^{\prime \prime }+n^{4} y = \sin \left (k x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime } = \left (2 x^{2}+x \right ) {\mathrm e}^{-2 x}+5 \cos \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y = 5 \,{\mathrm e}^{2 x} \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-4 y^{\prime } = \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime \prime }-5 y^{\prime } = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime } = {\mathrm e}^{2 x}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+y^{\prime }-4 y = \sin \left (x \right )-{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-4 y = 4 \,{\mathrm e}^{x}+3 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime \prime }-5 y^{\prime } = x^{2} {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime } = {\mathrm e}^{x} \left (\sin \left (x \right )-x^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime } = {\mathrm e}^{2 x} \left (x -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+9 y^{\prime \prime } = \sin \left (3 x \right )+x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = x^{2} {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime } = x^{2}+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y^{\prime }+2 y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = x^{3}-\frac {\cos \left (2 x \right )}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime \prime }+5 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime } = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = {\mathrm e}^{x}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+y^{\prime \prime \prime \prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime } = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime } = x \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-x y^{\prime }+y = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}4 x^{3} y^{\prime \prime \prime }+8 x^{2} y^{\prime \prime }-x y^{\prime }+y = x +\ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}3 x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }-10 x y^{\prime }+10 y = \frac {4}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+7 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }-6 x y^{\prime }-6 y = \cos \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }-x y^{\prime }+4 y = \sin \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-12 y^{\prime }+16 y = 32 x -8
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime \prime }+2 \left (y+3 y^{\prime }\right ) y^{\prime \prime }+2 {y^{\prime }}^{2} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime \prime }+2 y^{\prime \prime } = A x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = 6 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = 4 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-10 y^{\prime }+8 y = 24 \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+5 y^{\prime \prime }+6 y^{\prime } = 6 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-5 y^{\prime }-6 y = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 9 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 2 \,{\mathrm e}^{-x}+3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+y = 4 x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+104 y^{\prime \prime \prime }+2740 y^{\prime \prime } = 5 \,{\mathrm e}^{-2 x} \cos \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = \frac {2 \,{\mathrm e}^{x}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 36 \,{\mathrm e}^{2 x} \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = \frac {2 \,{\mathrm e}^{-x}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+9 y^{\prime } = 12 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+25 y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+25 y^{\prime } = \sin \left (4 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime \prime }+24 y^{\prime }+16 y = 8 \,{\mathrm e}^{-x}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-4 y^{\prime }+4 y = 2 x^{2}-4 x -1+2 x^{2} {\mathrm e}^{2 x}+5 \,{\mathrm e}^{2 x} x +{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+10 y^{\prime \prime }+9 y = \cos \left (2 x +3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right )+x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+4 y^{\prime }-8 y = {\mathrm e}^{2 x} \sin \left (2 x \right )+2 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+3 y^{\prime } = x^{2}+{\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime } = 7 x -3 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = \sin \left (x \right ) \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-3 y^{\prime \prime \prime }+y = 9 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 48 x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime } = 9 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime } = 7+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y = 64 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }-y = 44 \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+5 y^{\prime }+5 y = 5 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 4 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|